Lighting in the Performance "Kapai-Kapai" by Arifin C Noer - Koswara, Puji (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
This article focuses on lighting using GrandMA2 equipment, the work steps of a lighting designer, and the simulation of lighting arrangement work in the performance "Kapai-Kapai" by Arifin C Noer. This study aims to make lighting designs in theater performances with the script "Kapai-Kapai" by Arifin C Noer. This research is a type of action research that uses a qualitative approach, with library research methods to collect information, theories, and concepts related to lighting in the performing arts, especially theater. Research data sources include books related to performing arts, journal articles, and documents related to the performance "Kapai-Kapai." Meanwhile, data collection was obtained from observation and interviews. Data analysis is carried out qualitatively. Observational and interview data were analyzed to identify patterns, trends, and findings related to the application of lighting in the performance of "Kapai-Kapai." Modern equipment such as color-adjustable LED lights, special effects with projection, and automatic control allow performances to become even more dynamic and creative. Some lighting designers use computer simulations to plan light effects before the show begins. This allows them to test various scenarios and ensure that the lighting matches the artistic vision.